HUBUNGAN KELENGKAPAN IMUNISASI DASAR DENGAN STATUS GIZI PADA ANAK BAWAH DUA TAHUN - Niken Ayuningtyas; Lily Marliany Surjadi (Fakultas Kedokteran Universitas Trisakti, 2024)
In Indonesia, many infectious diseases which were found in children, that actually can be prevented by immunization. Therefore, immunization have been a government’s strategy to improve health quality, especially in children under 5 years old. By completing basic immunization in the first two years of a children’s life, the immune system of the body will improve so that preventing the children from many infectious diseases and will result in better nutritional status. This study was performed to obtain the relationship of complete basic immunization with nutritional status in children under 2 years (toddlers) in Kuningan, West Java. Data were collected cross sectionally from 150 toddlers met the inclusion criteria, using Kartu Menuju Sehat (KMS) and sigiziterpadu.kemenkes.go.id report. Data were then analyzed using Statistical Packages for Social Sciences (SPSS) for Mann-Whitney analysis. Result showed that most toddlers (94%) have a good nutritional status and 84.7% completed basic immunization before 2 years. Statistical analysis showed no relationship between basic immunization completion and nutritional status using parameters weight/age (p=0.213), body length/age (p=0.069) and weight/length (p=0.221)